TORONTOY: STAGES OF A PEOPLE THROUGH TIME - Gallegos Gutiérrez, Homar (2012)
History has shown us that societies have been through stages of change since they started, a splendor stage and a slope stage, but they has not disappeared, they have adapted to abrupt changes emerging new societies with different features where this cycle has been starting again. This has been happening in Peru from ancestral times, not long ago, during the Late Intermediate, there were some societies that ruled not very large territories (compared to the ones that later the Inkas would dominate) where they had their own social and structural codes; when the Inkas arrived, those patterns were taken up or modified according to the necessities of this new social power which also presented its own social codes. The same thing happened at the arrival of the European invaders in the XVI century. Architecture in Torontoy is very complex due to the modifications that have taken place during the historical stages; each period has particular and complex features and each architectural modification teaches us something about the management of their society because the architectonic change is not only in structure but in concept.